NONVERBAL MEANS OF COMMUNICATION - Shamsiyeva Gulchiroy (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
Nonverbal communication plays a crucial role in human interaction, often conveying more meaning than spoken words. This article explores the various types of nonverbal communication and their significance in conveying emotions, attitudes, and intentions. It categorizes nonverbal means into key types such as kinesics (body language), proxemics (use of space), haptics (touch), chronemics (use of time), facial expressions, eye contact, gestures, and paralanguage (vocal elements other than speech). Through theoretical analysis and practical examples, the study highlights how these forms function across different cultural and social contexts. Understanding nonverbal cues not only enhances interpersonal communication but also contributes to effective teaching, leadership, and cross-cultural competence.